Adapting to urban gardening in China: how will policymaking help migrant and native gardeners? - Xie, Yusi; Xing, Zhong (Frontiers in Sustainable Food Systems, 2024)
China’s current urban gardening promotion policies mainly focus on community gardens and lack in-depth research on the differentiated needs of different urban gardeners. To meet the diverse needs of China’s gardeners, this study proposes a typology that classifies gardeners into urban native and migrant ones based on their urban and rural living experiences in China. A questionnaire survey conducted in the core area of Chongqing city revealed significant differences and some similarities in gardening motivations and behaviors between urban native and migrant gardeners: (1) Although most of the gardeners approved of the value of food production and green scenery creation that Chinese urban gardening has, and disapproved of its value for family income generation, the urban native gardeners’ disapproving attitude towards family income generation, and their approval of green scenery creation were more assertive, while on the contrary, the urban migrant gardeners had a more robust approval attitude towards food production. (2) The urban native gardeners preferred proximity and small private spaces for a combination of ornamental vegetation and edible vegetables. In contrast, the urban migrated gardeners preferred larger areas for gardening in non-community spaces and leaned towards edible vegetables. (3) Both have shared motivations related to the recreation and ecological conservation values of urban gardening. Given the above differences and similarities, this paper proposes an urban gardening development strategy that meets the needs of the two types of gardeners in China, including space planning and design, operation, and management of gardening spaces, and organization of activities.